Sharia Compliance in Online Sales Transactions Using the Pre-order System on Shopee - Mawarni Lubis; Annisa Safitri; Luthfi Hariri; Salim Marzuki; Aqilla Annaufal (Sekolah Tinggi Agama Islam Solok Nan Indah, 2026)
The increasing use of the pre-order (PO) system on e-commerce platforms requires an assessment of its compliance with Sharia principles. However, pre-order practices may still give rise to ambiguity in product information and uncertainty regarding the delivery of goods, potentially involving elements of gharar, tadlis, and dharar. This study aims to analyze the characteristics of pre-order transactions on the Shopee platform and evaluate their compliance with Sharia principles from the perspectives of fiqh muamalah and maqasid al-shariah. The study employs a qualitative method with an exploratory approach through content analysis. Secondary data obtained from books, scholarly journals, academic literature, and relevant legislation were analyzed using a descriptive qualitative approach to examine the validity and Sharia compliance of pre-order transactions on the Shopee platform. The findings indicate that pre-order transactions on the Shopee platform represent a form of e-commerce in which goods are ordered and paid for in advance before they are physically available. Although this practice generally fulfills several indicators of Sharia compliance, it still has the potential to involve elements of gharar, tadlis, and dharar due to ambiguous information and uncertainty regarding the delivery of goods. From the perspective of maqasid al-shariah, pre-order transactions can be regarded as consistent with the objectives of Sharia, particularly in safeguarding wealth (hifz al-mal) and promoting the public interest (maslahah), provided that they are conducted transparently, honestly, and with clear certainty regarding the rights and obligations of all parties involved